2016
DOI: 10.1111/1346-8138.13352
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic features of steatocystoma simplex on the abdomen

Abstract: Dear Editor, Steatocystoma, originating from nevoid malformations of the pilosebaceous duct junction, is classified into steatocystoma multiplex (SCM) and steatocystoma simplex (SCS). The clinical manifestations of SCM differ from those of SCS: SCS is a single lesion that usually develops on the head or neck, while SCM develops on the trunk or extremities and is often inherited as an autosomal dominant trait. Brownstein described 30 cases of SCS in 1982. 1 Eleven lesions were present on the face, and the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…A debris‐fluid level can be seen if both liquid and keratinous materials are present. A doughnut‐shaped appearance, namely hypoechoic lesion in the center of an isoechoic cyst, has also been described . In our cases, SM lesions appeared on ultrasonography as hypoechoic nodules with well‐defined hyperechoic borders and, in case of liquid content, posterior acoustic enhancement, in the absence of Color Doppler signal.…”
Section: Discussionsupporting
confidence: 62%
“…A debris‐fluid level can be seen if both liquid and keratinous materials are present. A doughnut‐shaped appearance, namely hypoechoic lesion in the center of an isoechoic cyst, has also been described . In our cases, SM lesions appeared on ultrasonography as hypoechoic nodules with well‐defined hyperechoic borders and, in case of liquid content, posterior acoustic enhancement, in the absence of Color Doppler signal.…”
Section: Discussionsupporting
confidence: 62%
“…The nonhereditary counterpart to steatocystoma multiplex is steatocystoma simplex, a solitary lesion that can be situated on the face, scalp, neck, axillae, chest, upper limbs, back, and lower limbs, with no family history, and an onset during adulthood. 23,24 There are few ultrasonographic reports of steatocystomas in the literature. The scarce reports found show them as well circumscribed nodules with heterogeneous echogenicity and lateral shadows.…”
Section: Steatocystomamentioning
confidence: 99%
“…A "doughnut" shape has been described, with a small central hypoechoic cystic lesion. 24 Other authors define them as well-defined cysts with internal echoes. 25 In our series we observed they are most frequently located in the subcutaneous tissue and less commonly in the dermis (Figure 8, A-C).…”
Section: Steatocystomamentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasonographic findings of steatocystomas have been reported in a limited number of studies ( 7 8 9 10 11 ), three of which reported mammographic and ultrasonographic findings of steatocystoma multiplex occurring in the breast. Park et al ( 10 ) reported the ultrasound findings of steatocystoma multiplex in four patients; sonographic findings revealed multiple well-circumscribed homogeneous lesions that either confined to the dermal layer or involved the subcutaneous fat.…”
Section: Introductionmentioning
confidence: 99%